The effect of laser irradiation on the viability of human breast cancer cell, MDA-MB-231 - Badruzzaman, A. (Penerbit UTM Press, 2016)
A practical pass-through type fibre Bragg grating (FBG) temperature sensor system have been designed, developed, simulated, and experimentally investigated. The performance of FBG was evaluated in harsh environments exposed under direct sunlight, rain, and wind. The sensor system designed directly focused with convex and hand lens. The temperature of FBG’s sensor head been measured. The broadband laser source was launched into the system using tunable laser source (TLS) and both transmission and reflection spectra of FBG sensor were measured by optical spectrum analyzer (OSA). Results shows that the Bragg wavelength shift, ΔλB increased proportionally with the temperature changes. The sensitivity of FBG were recorded at 0.0100 and 0.0132 nm °C-1 for the systems where convex and hand lens applied to the FBG’s sensor head respectively, while the sensitivity of 0.0118 nm °C-1 measured for the system without any focusing element applied.